The Brain-Dead Organ Donor (2012)
Addressing all aspects of brain death and thoroughly detailing how a potential organ donor should be maintained to ensure maximum use of the organs and cells, The Brain-Dead Organ Donor: Pathophysiology and Management is a landmark addition to the literature. This first-of-its-kind, multidisciplinary volume will be of interest to a large section of the medical community. The first section of the book reviews the historical, medical, legal, and ethical aspects of brain death. That is followed by two chapters on the pathophysiology of brain death as investigated in small and large animal models. This includes a review of the many hormonal changes, including the neuroendocrine- adrenergic ‘storm’, that takes place during and following the induction of brain death, and how they impact metabolism. The next section of the book reviews various effects of brain death, namely its impact on thyroid function, the inflammatory response that develops, and those relating to innate immunity. The chapters relating to assessment and management of potential organ donors will be of interest to a very large group of transplant surgeons and physicians as well as critical care and neurocritical care physicians and nurses. Neurologists, endocrinologists, neurosurgeons, and pathologists will also be interested, especially in the more basic science sections on various aspects of brain-death and hormonal therapy. Organ procurement organizations and transplant coordinators worldwide will also be interested in this title. Other chapters will be of interest to medical historians, medico-legal experts, and ethicists.